1998
DOI: 10.1021/la970802g
|View full text |Cite
|
Sign up to set email alerts
|

Micron-Sized Protein Patterning on Diazonaphthoquinone/Novolak Thin Polymeric Films

Abstract: Protein patterns at 2-μm resolution were surface-printed on the unprofiled surface of diazonaphthoquinone/novolak thin polymeric films through positive-tone and reversed negative-tone lithography. The possible mechanisms responsible for selective protein patterning, that is, (i) linkage of the amino end of the protein to the photoinduced indenecarboxylic acid via NH2-to-COOH cross-linking mediated by carbodiimide, (ii) linkage of the amino end of the protein via in-situ addition to the photoinduced ketene, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 26 publications
0
34
0
3
Order By: Relevance
“…Polymeric surfaces, in particular photosensitive polymers with light-tunable properties [25], of which PtBMA is a member [26], have previously been used to probe the surface-induced metabolic change of surface-anchored marine bacteria [27]. Compared to other polymers, PtBMA has certain experimental advantages, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Polymeric surfaces, in particular photosensitive polymers with light-tunable properties [25], of which PtBMA is a member [26], have previously been used to probe the surface-induced metabolic change of surface-anchored marine bacteria [27]. Compared to other polymers, PtBMA has certain experimental advantages, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Preferably, however, the integration of enzyme functionality into MEMS should be accomplished using existing microfabrication techniques, and is compatible with established processes. Protein immobilization on photoresists provides a method with perfect process compatibility and versatile patterning possibilities (Blagoi et al 2008;Ganesan et al 2008;Nicolau et al 1998). However, up to now special conjugation methods have been required, such as light-promoted protein attachment (Nicolau et al 1998) or chemical modification of the photoresist surface (Blagoi et al 2008;Ganesan et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…7,13,14 Most of the studies developed have focused on forming arrays of single proteins. 7,8,[15][16][17][18][19][20] However, few studies have reported engineering of multiple protein arrays on surfaces and have various limitations including pattern resolution, 21,22 protein degradation, 23 and exposure to harsh chemicals. 24 In this study, we engineered a novel salt tunable resistive m-dPEG acid SAM patterns on PEM surfaces which provides a template to design numerous sorted surfaces that can be used in a wide variety of applications.…”
Section: Introductionmentioning
confidence: 99%